Carboxylesterase3 (Ces3) Interacts with Bone Morphogenetic Protein 11 and Promotes Differentiation of Osteoblasts via Smad1/5/9 Pathway - Mukherjee, Sulagna; Park, Jong Pil; Yun, Jong Won (Biotechnology and bioprocess engineering, 2022)
Ces3 is a lipolytic enzyme predominantly present in liver and adipocytes, with recent reports of its presence in skeletal muscles, as well. A cross-linking study to understand the various interacting proteins involved in bone-adipose axis could provide novel targets for drug development. We explored the functional role of Ces3 in osteoblasts and mesenchymal stem cells differentiating into osteoblast lineage using in vitro models. We also investigated the physiological functions of Ces3 by stable gene knockdown of Ces3 and exogenous Ces3 induction, and examined the interacting proteins by Co-IP and in-silico analysis. Data from our study suggests that Ces3 is highly expressed in osteoblasts and promotes proliferation of the cells by increasing the expressions of osteogenic marker proteins and genes. For the first time, our mechanistic studies revealed that Ces3 interacts with BMP11 protein for regulation of osteoblast differentiation and activates the ALK2 and BMP type II receptors via Smad 1/5/9 signaling pathways. In addition, we identified the various partner proteins linked to Ces3 and BMP11 which are also involved in the metabolic network of osteoblasts. In silico analysis revealed a direct and strong interaction between Ces3 and BMP11 which influences the growth and regulation of osteoblasts. Current data unveiled a hitherto unknown mechanism of Ces3 and BMP11 in the bone-adipose axis, shedding light on Ces3 as a pharmacotherapeutic target to treat metabolic disorders.